2020
DOI: 10.1093/tas/txaa013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combinations of feed-grade urea and slow-release urea in a finishing beef diet on fermentation in an artificial rumen system

Abstract: This study evaluated the effect of combinations of feed-grade urea and slow-release urea (SRU) on fermentation and microbial protein synthesis within two artificial rumens (Rusitec) fed a finishing concentrate diet. The experiment was a completely randomized, dose–response design with SRU substituted at levels of 0% (control), 0.5%, 1%, or 1.75% of dry matter (DM) in place of feed-grade urea, with four replicate fermenters per dosage. The diet consisted of 90% concentrate and 10% forage (DM basis). The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…The absent effect of increasing the dose of SRU in the diets from 0, 0.28 to 0.56% on nutrient digestibility is in agreement with some studies [7,28,29], but it is consistent with other studies [9,30]. With using continuous culture system, Xin et al [7] found no differences in the nutrient digestibility of corn-based dairy cow diet supplemented with either feed grade urea or polyurethane coated urea.…”
Section: Effects Of Sru On Nutrient Disappearance Gassupporting
confidence: 84%
See 3 more Smart Citations
“…The absent effect of increasing the dose of SRU in the diets from 0, 0.28 to 0.56% on nutrient digestibility is in agreement with some studies [7,28,29], but it is consistent with other studies [9,30]. With using continuous culture system, Xin et al [7] found no differences in the nutrient digestibility of corn-based dairy cow diet supplemented with either feed grade urea or polyurethane coated urea.…”
Section: Effects Of Sru On Nutrient Disappearance Gassupporting
confidence: 84%
“…Gardinal et al [29] reported that the nutrient digestibility in the total digestive tract was not affected by adding 2% polymercoated SRU in the diet of Nellore steers. In contrast, Alipour et al [9] reported quadratically increased the digestibility of NDF and ADF of a high concentrate diet with increasing SRU dosages from 0, 0.5, 1.0 to 1.75% in high concentrate diet in Rusitec. Another study has been demonstrated to increase total tract DM and CP digestibility when fed polymer-coated SRU to lactating dairy cows [6].…”
Section: Effects Of Sru On Nutrient Disappearance Gasmentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, there is limited published information on the effect of feeding urea on real enteric CH 4 production. Alipour et al (2020) [42], and Rebelo et al (2019) [43] showed that feeding two sources of coated and non-coated urea did not affect enteric CH 4 yield measured in an in vitro ruminal fermentation system or beef cattle, respectively. However, Libera et al (2021) showed that the CH 4 production at the ruminal level reduced after using urea combined with enzymes and cereals in dairy cows.…”
Section: Characteristics Of the Diets Feces And Digestibility Of The Feedsmentioning
confidence: 99%